A comprehensive review on pathogenesis, associations, clinical findings, and treatment of livedoid vasculopathy - Seguí, Mireia; Llamas-Velasco, Mar (Frontiers in Medicine, 2022)
Livedoid vasculopathy (LV) is a thrombo-occlusive vasculopathy that involves the dermal vessels. Clinically, it is characterized by the presence of painful purpuric ulcers on the lower extremities. Histopathologically, it shows intraluminal fibrin deposition and thrombosis, segmental hyalinization and a later endothelial proliferation. It is important to notice that the term “atrophie blanche” is descriptive and it includes not only patients with LV but also patients with a combination of vasculitis and vasculopathy, that is, LV and medium-size vasculitis such as cutaneous polyarteritis. (PANc) Diagnosis is based in a proper clinico-pathological correlation excluding the main differential diagnosis and considering vasculitis as mimickers or concomitant diagnosis. Coagulation disorders, must be studied although there are not found in all LV. Its frequency is reviewed. Treatment of LV is a challenge and many therapies have been tried. Pain management, wound care, control of cardiovascular risk factors and both antiplatelets and anticoagulants, mostly rivaroxaban, are the main therapies used. The different therapies as well as their degree of evidence are reviewed.